Efficiency analysis of ultrasound diagnosis of acute appendicitis during pregnancy - Petrashenko, Inna; Loskutova, Tetiana (ScienceRise: Medical Science, 2020)
The aim of the study was to identify ultrasound signs of various forms of the acute appendicitis and to study the efficiency of the ultrasound method in the diagnosis of acute appendicitis in pregnant women. Materials and methods. 73 pregnant women (group I) and 43 non-pregnant women (group II) were examined with suspicion of acute appendicitis. The age of patients ranged from 18 to 40 years, on average – 25.7± 0.5 years. Gestational age was from 4–5 to 35–36 weeks. The informational content of sonography was studied by following criteria: sensitivity, specificity, accuracy and efficiency. Results and discussion. An analysis of the results of informational content showed that the diagnostic significance of ultrasound by the third trimester of gestation is decreased which is probably due to the increased size of the uterus and the appearance of acoustic difficulties. Sensitivity, accuracy and efficiency were higher in the first trimester in contrast with second and third trimesters. In group II, higher values of informative indices were noted than in women of group I. There is an increase: sensitivity by 27.3 %, accuracy by 25.2 % and diagnostic efficiency by 14.7 %. Conclusions. Ultrasound diagnosis of acute appendicitis during pregnancy especially at the end of II and III trimesters is a definite problem points to the advantages of an integrated approach to the diagnosis of acute appendicitis during pregnancy comparing the clinical manifestations of the disease with the results of diagnostic research methods